Comparative mitogenomes provide new insights into phylogeny and taxonomy of the subfamily Xenocyprinae (Cypriniformes: Cyprinidae) - Zhang, Zhi; Li, Jiming; Zhang, Xiaodong; Lin, Bingming; Chen, Jianming (Frontiers in Genetics, 2022)
Xenocyprinae is a cyprinid subfamily that not only has a discrete geographic distribution but also has a long history dating to the Early Miocene. However, it is controversial whether systematic classification and some species validity of Xenocyprinae exist, as well as its phylogenetic relationships and evolutionary history. In the present study, we first reviewed the description and taxonomic history of Xenocyprinae. And then, the complete mitochondrial genome of Distoechodon compressus, an endemic and locally-distributed species belonging to Xenocyprinae, was sequenced and annotated. Finally, all the mitogenomes of Xenocyprinae were compared to reconstruct the phylogenetic relationship and estimate the divergence time. The results showed that the mitogenomes are similar in organization and structure with 16618 to 16630 bp in length from 12 mitogenomes of 8 species. Phylogenetic analysis confirmed the monology of Xenocyprinae and illustrated three clades within the Xenocyprinae to consist of ambiguous generic classification. Plagiognathops is a valid genus located at the base of the phylogenetic tree. The genus Xenocypris was originally monophyletic, but X. fangi was excluded. Divergence time estimation revealed that the earliest divergence within Xenocyprinae occurred approximately 12.1 Mya when Plagiognathops separated from the primitive Xenocypris. The main two clades (Xenocypris and (Distoechodon + Pseudobrama + X. fangi)) diverged 10.0 Mya. The major divergence of Xenocyprinae species possibly occurred in the middle to late Miocene and late Pliocene, suggesting that speciation and diversifications could be attributed to the Asian monsoon climate. This study clarifies some controversial issues of systematics and provides essential information for the taxonomy and phylogeny of the subfamily Xenocyprinae.